The net cash flow indicator of the order portfolio as an indicator of the contractor economic reliability - D. A. Borisyuk; O. E. Astafieva (Вестник университета, 2021)
Modern information transparency of the results of organizations’ activities determines the use of non-standard tools of financial and economic analysis. The purpose of the article is to show the variety of such tools as the main element used to assess the reliability of a contracting organization. A non-standard approach to the analysis of the sufficiency of free cash from operating activities and the efficiency of the use of working capital, taking into account the peculiarities of the contractor’s activities, is illustrated. The object of the study is the indicators of free cash flow from operating activities. The subject of the study is the features of the activities of contracting companies that determine the possibility of using a non-standard approach in analysing financial condition of organizations of this profile. The article reveals the differences between the widely used EBITDA indicator and the considered indicator of the net cash flow of the order portfolio.